Improved arterial flow-mediated dilation after exertion involves hydrogen peroxide in overweight and obese adults following aerobic exercise training. Issue 7 (July 2016) - Robinson, Austin T.; Franklin, Nina C.; Norkeviciute, Edita; Bian, Jing Tan; Babana, James C.; Szczurek, Mary R.; Phillips, Shane A.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Acute strenuous physical exertion impairs arterial function in sedentary adults. We investigated the effects of 8 weeks of regular aerobic exercise training on acute physical exertion-induced arterial dysfunction in sedentary, overweight, and obese adults. Methods: Twenty-five overweight and obese adults (BMI 30.5 ± 7.2 years) were assigned to 8 weeks of aerobic training or to a control group. Brachial artery flow-mediated dilation (FMD) was assessed before and after acute leg press exercise at weeks 0 and 8. Gluteal adipose biopsies were performed at rest and post acute leg press to measure microvessel FMD with and without nitric oxide synthase inhibition vial NG -nitroarginine methyl ester or hydrogen peroxide (H2 O2 ) scavenging with Catalase. Microvessel nitric oxide and H2 O2 production were assessed via fluorescence microscopy. Results: Brachial artery dilation was reduced post acute leg press at week 0 in the aerobic exercise and control groups, but was preserved in the aerobic-exercise group post acute leg press at week 8 ( P < 0.05). Post acute leg press microvessel FMD was preserved in the aerobic exercise group but impaired in the control group at week 8 ( P < 0.05). Preserved dilation in the aerobic exercise group was more sensitive to H2 O2 scavenging than inhibition of nitric oxide, and post acute leg press microvessel H2 O2 production was increased compared with at rest ( P < 0.05). Conclusion: Aerobic exercise prevents acute exertion-induced arterial dysfunction in overweight and obese adults via a phenotypic switch from nitric oxide-mediated dilation at rest to a predominately H2 O2 -mediated dilation after acute physical exertion.